2016
DOI: 10.1021/acs.biochem.6b00576
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Kinetic Analysis of Two Conformationally Restricted Peptide Substrates of Escherichia coli Penicillin-Binding Protein 5

Abstract: Escherichia coli PBP5 (penicillin-binding protein 5) is a dd-carboxypeptidase involved in bacterial cell wall maturation. Beyond the C-terminal d-alanyl-d-alanine moiety, PBP5, like the essential high-molecular mass PBPs, has little specificity for other elements of peptidoglycan structure, at least as elicited in vitro by small peptidoglycan fragments. On the basis of the crystal structure of a stem pentapeptide derivative noncovalently bound to E. coli PBP6 (Protein Data Bank entry 3ITB ), closely similar in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…7A ). Analysis of this structure revealed binding of the substrate but not the closed conformation needed for hydrolysis ( 17 ). Indeed, kinetic studies found that PBP6a does not hydrolyze the substrate used for the crystal structure ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7A ). Analysis of this structure revealed binding of the substrate but not the closed conformation needed for hydrolysis ( 17 ). Indeed, kinetic studies found that PBP6a does not hydrolyze the substrate used for the crystal structure ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…d , d -CPase inhibitors have been developed using PBP5 as a model enzyme by generating specific substrates like cyclic peptides or boronates ( 17 , 18 ). Although single deletions of d,d -CPases elicit only mild phenotypes in E. coli , the additional deletion of multiple enzymes results in cells that are unable to maintain their morphology, suggesting at least partly complementing functions ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%